Oral Ibuprofen Versus Oral Paracetamol in Pain Management During Screening for Retinopathy of Prematurity: A Prospective Observational Study. Issue 3 (July 2022) - Bulut, Ozgul; Tarak Bozkurt, Ozge; Arslanoglu, Sertac
Abstract : Screening examinations for retinopathy of prematurity (ROP) are critical to reduce ROP-related vision loss; however, the procedure is painful and uncomfortable, and topical anesthetics do not completely suppress the pain responses. The number of safe and effective pharmacological options to reduce pain during eye examinations for ROP screening in preterm infants is limited. This study compared the efficacy of oral ibuprofen and oral paracetamol in reducing pain during screening for ROP in preterm infants. This prospective observational study was conducted at a tertiary-care neonatal intensive care unit. Forty-four preterm infants with gestational age of 32 weeks and less undergoing ROP screening were included. Each enrolled infant received either oral ibuprofen 10 mg/kg ( n = 22) or oral paracetamol 10 mg/kg ( n = 22) 1 hour before eye examination. The primary outcome measure was pain assessed by the Neonatal Pain, Agitation, and Sedation Scale (N-PASS). Secondary outcome measures were tachycardia, bradycardia, desaturations, and crying time. The groups were similar for gestational age, birth weight, and postnatal age at examination ( P > .05). The mean N-PASS scores were not significantly different between the oral ibuprofen and oral paracetamol groups (8.64 ± 1.57 vs 8.50 ± 1.71, respectively, P = .605). Moreover, no significant intergroup differences were observed in the crying time and the incidence of tachycardia/bradycardia and desaturation ( P > .05). Ibuprofen or paracetamol administered orally before ROP screening in preterm infants had similar analgesic effects and did not significantly alleviate pain during eye examination.